The effect acupressure therapy on breast milk volume in postpartum mothers - Fiya Diniarti; Diyah Tepi Rahmawati; Idris Adewale Ahmed (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Breast milk is the main source of food for the growth and development of infants.  The lack of breast milk is one of the obstacles to the adequate utilization of this substancei. One of the treatments that can help address this issue is acupressure. Purpose: To determine the effect of acupressure theraphy on breast milk volume in postpartum mothers. Method: A descriptive quantitative with quasi-experimental specially focusing on pretest-posttest control group. The study took place from April to May 2025 in Bengkulu. The independent variables studied were acupressure therapy, while the dependent variable was breast milk volume. Using accidental sampling and slovin formula 30 participants were selected divided into 2 group included intervention and control group, who meet specific inclusion and exclusion criteria. The analysis proceeded with a univariate test to determine the frequency distribution of respondent’s characteristics, followed by bivariate analysis using mann whitney test. Results: The intervention group had a mean value (Mean±SD) of 10.5±8.3, while the control group showed a lower value of 6.33±4.3. The statistical test produced a p-value of 0.004, which means that there was a significant difference between the two groups (p < 0.05). Conclusion: That acupressure intervention was more effective in increasing breast milk volume than standard care in the control group.